1992
DOI: 10.1182/blood.v80.8.2012.2012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of granulocyte survival and programmed cell death by cytokines and bacterial products

Abstract: Mature circulating polymorphonuclear cells (PMN) have the shortest half- life among leukocytes and undergo rapid programmed cell death in vitro. In this study, we have examined the possibility that inflammatory signals (cytokines and bacterial products) can regulate PMN survival. PMN in culture were found to rapidly die, with percentages of survival at 24, 48, 72, and 96 hours of 97.3% +/- 1.9%, 36.8% +/- 5.3%, 14.5% +/- 3.1%, and 4.2% +/- 2.9%, respectively (mean +/- SE of 20 different donors). PMN incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
272
4
8

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,010 publications
(293 citation statements)
references
References 34 publications
9
272
4
8
Order By: Relevance
“…Stojanov and colleagues demonstrated that the levels of IL-1␤ mRNA were increased during PFAPA syndrome flares (10). Although this finding was not corroborated by a finding of increased levels of IL-1␤ protein in the serum (9-11), the results of our studies and those of other investigators have suggested that IL-1␤ may regulate apoptosis (48)(49)(50). In a recent study by Blomgran et al, increased IL-1␤ plasma levels were detected in patients with genetic variations in the NALP3 inflammasome, correlating with decreased rates of PMN apoptosis (48).…”
Section: Discussioncontrasting
confidence: 76%
“…Stojanov and colleagues demonstrated that the levels of IL-1␤ mRNA were increased during PFAPA syndrome flares (10). Although this finding was not corroborated by a finding of increased levels of IL-1␤ protein in the serum (9-11), the results of our studies and those of other investigators have suggested that IL-1␤ may regulate apoptosis (48)(49)(50). In a recent study by Blomgran et al, increased IL-1␤ plasma levels were detected in patients with genetic variations in the NALP3 inflammasome, correlating with decreased rates of PMN apoptosis (48).…”
Section: Discussioncontrasting
confidence: 76%
“…Infectious and heat-inactivated RSV directly inhibits PMN apoptosis through activation of PI3Kand NF-kB-dependent prosurvival pathways (28). Furthermore, RSV induces expression of IL-6 by PMNs, which may provide autocrine regulation of PMN survival (28,34,35). In contrast to RSV, influenza A virus enhances PMN apoptosis in vitro (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CXC chemokines, PMN apoptosis is also inhibited by cytokines, including GM-CSF, G-CSF, IL-1b, IL-6, IFN-g, TNF-a, and IL-15 (35,39,40). In contrast, other proinflammatory cytokines, such as TNF-a and IL-6, significantly induce PMN apoptosis (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils released to blood circulation have a half-life of 8 to 10 h. If not activated, these cells are destined for apoptosis (Savill, 1997). Stimulation of neutrophils with proinflammatory cytokines such as granulocyte macrophage-colony-stimulating factor, G-CSF, and IL-1␤, but not with fMLF, C5a, or IL-8, prolongs the lifespan of neutrophils (Colotta et al, 1992). Other reports have shown that stimulation of neutrophils with fMLF can induce apoptosis, and this process requires superoxide generation (Kettritz et al, 1997).…”
Section: Transcriptional Regulation and Anti-inflammatorymentioning
confidence: 99%